Artificial solid electrolyte interface allowing ethylene carbonate free electrolytes in lithium ion batteries

By depositing the LBCO coating formed by ALD on the surface of the electrode of the lithium-ion battery, the cost of natural SEI formation during the lithium-ion battery is solved, and the cycle life and manufacturing cost efficiency is improved under the electrolyte without ethylene carbonate. .

CN119422257APending Publication Date: 2025-02-11THE RGT UNIV OF MICHIGAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380048807.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-04
Filing Date
2023-05-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing lithium-ion batteries require expensive natural SEI formation during the synthesis process, and the cycle life is shortened and the manufacturing cost is high when using electrolytes that do not contain ethylene carbonate.

Method used

The lithium-lithium borate-lithium carbonate (LBCO) solid electrolyte coating formed by atomic layer deposition (ALD) is deposited on the surface of the lithium-ion battery electrode, eliminating natural SEI formation and allowing the use of electrolytes without ethylene carbonate.

Benefits of technology

It improves the first cycle efficiency of lithium-ion batteries, reduces the need for pre-regulation, improves electrolyte infiltration, extends cycle life, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119422257A_ABST
    Figure CN119422257A_ABST
Patent Text Reader

Abstract

A method of forming an electrochemical device may comprise the steps of: (a) exposing electrode material particles to a lithium-containing precursor followed by an oxygen-containing precursor, thereby forming a coating on the electrode material particles; (b) forming a slurry comprising the coated electrode material particles; (c) casting the slurry to form a layer; (d) calendering the layer to form one or more electrodes (anodes and / or cathodes); (e) disposing a separator between the anode and the cathode to form a unit cell structure; and (f) disposing the cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the anode and / or cathode. The process reduces the need for slow, expensive pre-regulation after assembly of the lithium ion battery cells and enables the use of ethylene carbonate-free electrolytes, thereby improving the cycling stability of the lithium ion battery at high voltages.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. patent application No. 63 / 338,157, filed on May 4, 2022.

[0003] Statement Regarding Federally Funded Research

[0004] This invention was made with government support under Grant No. DE-AR0000653 awarded by the U.S. Department of Energy. The government may have certain rights in this invention. Technical Field

[0005] The present invention relates to electrochemical devices, such as lithium ion battery electrodes, thin film lithium ion batteries and lithium ion batteries comprising these electrodes. Background Art

[0006] Lithium-ion batteries have become an essential component of society's ability to store and use electrical energy. Among numerous applications, electric vehicles (EVs) are rapidly becoming the dominant source of demand for rechargeable batteries. Despite significant progress over the past few years, further improvements in charging rate and energy density remain key challenges. Improving energy density and charging rate without sacrificing cycle life, safety or cost is a pressing challenge in battery development.

[0007] Existing electrolytes for lithium-ion batteries contain a mixture of organic solvents including ethylene carbonate (EC). EC is generally considered a requirement for the formation of a stable solid electrolyte interface on a graphite electrode. The solid electrolyte interface begins to form on the anode and cathode during the first charge in the formation process of a lithium-ion battery whose anode contains graphite and uses a liquid electrolyte containing a lithium salt (such as LiPF6) and ethylene carbonate solvent. Because lithiated carbon is unstable in air, this type of lithium-ion battery is assembled in its discharged, unformed state, which means using a graphite anode and a lithiated positive cathode material. With Li / Li +In contrast, electrolytes including ethylene carbonate solvents are thermodynamically unstable at low and very high potentials. Therefore, when the anode is exposed to an electrolyte solution including ethylene carbonate solvent and the first charging current of the formation process is applied to the battery, an immediate reaction occurs between the lithium ions and the ethylene carbonate solvent. The insoluble products of the parasitic reaction between lithium ions, anions and ethylene carbonate solvent are deposited on the anode surface and are regarded as a solid electrolyte interface (SEI). The SEI layer gives the electrolyte kinetic stability, preventing further degradation in continuous cycles, thereby ensuring good cyclability of the electrode. It is reported that the SEI thickness can range from a few angstroms to tens or hundreds of angstroms. Studies have shown that the SEI on a graphite anode is a dense layer of inorganic components close to the anode carbon, followed by a porous organic or polymer layer close to the electrolyte phase. The actual surface chemistry of the SEI layer in a given unit cell is usually obtained by characterization methods such as Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS).

[0008] Therefore, in the initial formation cycle of the manufacturing facility, ethylene carbonate is reduced and forms a passivating SEI layer on the electrode surface. This SEI layer confers kinetic stability to the electrolyte from further reduction in successive cycles, thereby ensuring good cyclability of the electrode. However, the formation cycle to form the SEI is costly in that it can account for about one-third of the manufacturing cost of a lithium-ion battery.

[0009] As an alternative to electrolytes including ethylene carbonate, electrolytes without ethylene carbonate are reported to provide superior high-voltage stability and ion conductivity for lithium-ion batteries. However, the use of electrolytes without ethylene carbonate generally results in a shortened cycle life when using graphite electrodes.

[0010] Therefore, there is a need for methods to improve the cycle life of lithium-ion batteries and reduce the manufacturing cost of lithium-ion batteries. Summary of the invention

[0011] We have developed a coating process that deposits a protective coating on the surface of lithium-ion battery electrodes prior to cell assembly. The coating, deposited by atomic layer deposition (ALD), contains a lithium borate-carbonate (LBCO) solid electrolyte. The coating passivates the electrode surface, preventing side reactions during charging and improving first cycle efficiency. Eliminating SEI formation also reduces the need for slow, expensive pre-conditioning using formation current after lithium-ion battery cell assembly. The LBCO coating also improves electrolyte wetting into the electrode, reducing the time required before pre-conditioning can begin. The LBCO coating allows the use of EC-free electrolytes, free of additives, thereby improving the cycling stability of lithium-ion batteries at high voltages.

[0012] In one aspect, the present disclosure provides a method for forming an electrochemical device. The method may include: (a) exposing anode material particles to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the anode material particles; (b) forming a slurry comprising coated anode material particles; (c) casting the slurry on a surface to form a layer; (d) calendering the layer to form an anode of the electrochemical device; (e) placing a separator between the anode and the cathode to form a unit cell structure; and (f) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the anode. An exemplary solvent that can form a solid electrolyte interface on the anode can be a carbonate, such as ethylene carbonate. Step (a) may further include: exposing the anode material particles to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the anode material particles. In the method, the coating may include Li3BO3-Li2CO3.

[0013] In another aspect, the present disclosure provides a method for forming an electrochemical device. The method may include: (a) forming a mixture comprising particles of an anode material; (b) casting and / or calendering the mixture to form a porous structure; (c) exposing the porous structure to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the porous structure, thereby forming an anode; (d) placing a separator between the anode and the cathode to form a unit cell structure; and (e) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the anode. An exemplary solvent that can form a solid electrolyte interface on the anode may be a carbonate, such as ethylene carbonate. Step (c) may further include: exposing the porous structure to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the porous structure. In the method, the coating may include Li3BO3-Li2CO3.

[0014] In yet another aspect, the present disclosure provides a method for forming an electrochemical device. The method may include: (a) exposing cathode material particles to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the cathode material particles; (b) forming a slurry comprising coated cathode material particles; (c) casting the slurry on a surface to form a layer; (d) calendering the layer to form a cathode of the electrochemical device; (e) placing a separator between the cathode and the anode to form a unit cell structure; and (f) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the cathode. An exemplary solvent that can form a solid electrolyte interface on the cathode can be a carbonate, such as ethylene carbonate. Step (a) may further include: exposing the cathode material particles to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the cathode material particles. In the method, the coating may include Li3BO3-Li2CO3.

[0015] In still another aspect, the present disclosure provides a method for forming an electrochemical device. The method may include: (a) forming a mixture comprising cathode material particles; (b) casting and / or calendering the mixture to form a porous structure; (c) exposing the porous structure to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the porous structure, thereby forming a cathode; (d) placing a separator between the cathode and the anode to form a unit cell structure; and (e) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the cathode. An exemplary solvent that can form a solid electrolyte interface on the cathode may be a carbonate, such as ethylene carbonate. Step (c) may further include: exposing the porous structure to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the porous structure. In the method, the coating may include Li3BO3-Li2CO3.

[0016] One advantage of the present invention is that it provides a method that eliminates the expensive natural SEI formation required during the formation process of a lithium-ion battery having an anode comprising graphite and a liquid electrolyte comprising ethylene carbonate solvent.

[0017] Another advantage of the present invention is to provide a method that eliminates the natural SEI formation required during the formation process of a lithium ion battery having a cathode and a liquid electrolyte containing ethylene carbonate solvent.

[0018] Another advantage of the present invention is that it provides a method for increasing the coulombic efficiency of lithium ion batteries using electrolytes that do not contain ethylene carbonate over multiple cycles.

[0019] Another advantage of the present invention is that a method is provided that enables the use of lower N:P ratios in lithium ion batteries, where the N:P ratio is defined as the ratio of the reversible capacity of the negative electrode (N) to the reversible capacity of the positive electrode (P).

[0020] Yet another advantage of the invention is to provide a method that provides greater improvement in SEI stability than previously reported methods (eg, using vinylene carbonate additives).

[0021] Yet another advantage of the present invention is that it provides a method that improves high temperature operation of lithium ion batteries because the electrolyte coating passivates the electrodes and inhibits electrolyte interface side reactions, thereby improving capacity retention.

[0022] The above and other aspects and advantages of the present invention will be apparent from the following description. In the description, reference is made to the accompanying drawings which form a part of this article, in which exemplary embodiments of the present invention are shown by way of illustration. However, such embodiments may not represent the full scope of the present invention, and therefore, reference is made to the claims and text to interpret the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a schematic diagram of a thin-film lithium-ion battery.

[0024] Figure 2 A process flow diagram describing a method for making lithium borate-lithium carbonate thin films.

[0025] Figure 3 Depicted are the elimination of SEI formation on graphite by LBCO coating in an electrolyte without ethylene carbonate (EC) (in panels a and b), and the Coulombic efficiency of the initial pre-conditioning cycle (in panel c).

[0026] Figure 4 Depicted are the capillary rise of a carbonate-based electrolyte through a calendered electrode measured by optical image analysis (panel a), and images of the electrode immersed in the electrolyte, initially and after 200 seconds (panels b and c).

[0027] Figure 5 Depicted are the discharge capacity at upper cutoff voltages of 4.3 V and 4.5 V with and without LBCO coating, and the average Coulombic efficiency for the first 50 cycles at 1 C / 1 C charge / discharge rate at upper voltage cutoffs of 4.3 V and 4.5 V (inset c).

[0028] Figure 6X-ray photoelectron spectroscopy data of electrodes in the following electrode and electrolyte combinations are described: (i) uncoated electrode (Ctrl)-ethylene carbonate / ethyl methyl carbonate+vinylene carbonate; (ii) uncoated electrode (Ctrl)-ethyl methyl carbonate; (iii) LBCO-coated electrode-ethylene carbonate / ethyl methyl carbonate+vinylene carbonate; and (iv) LBCO-coated electrode-ethyl methyl carbonate.

[0029] Figure 7 The relationship between the discharge capacity and the number of cycles of unit cells having the following electrode and electrolyte combinations is described: (i) uncoated electrode (control)-ethyl methyl carbonate; (ii) LBCO-coated electrode-ethyl methyl carbonate; (iii) uncoated electrode (control)-ethyl methyl carbonate+vinylene carbonate; and (iv) uncoated electrode (control)-ethylene carbonate / ethyl methyl carbonate+vinylene carbonate.

[0030] The present invention will be better understood, and features, aspects and advantages other than those described above will become apparent when considering the following detailed description of the present invention, which refers to the accompanying drawings. DETAILED DESCRIPTION

[0031] Before explaining any embodiment of the present invention in detail, it should be understood that the present invention is not limited to the details of the construction and component arrangement described in the following specific embodiments or shown in the following figures when practiced. The present invention allows other embodiments and can be practiced or carried out in various ways. In addition, it should be understood that the wording and terminology used herein are only for descriptive purposes and should not be considered as restrictive. "Including", "comprising" or "having" and its variants used herein are intended to cover the items listed subsequently, and their equivalents, and other items.

[0032] The following is presented so that those skilled in the art can make and use embodiments of the present invention. Various modifications to the illustrated embodiments will be readily apparent to those skilled in the art, and the general concepts herein may be applied to other embodiments and applications without departing from embodiments of the present invention. Therefore, embodiments of the present invention are not intended to be limited to the illustrated embodiments, but rather to the widest range consistent with the concepts and features described herein. The skilled artisan will appreciate that the examples provided herein have a variety of useful alternatives and fall within the scope of embodiments of the present invention.

[0033] Although the systems and methods described herein are often described as being used in an electrochemical cell or battery, one skilled in the art will appreciate that these teachings may be used in a variety of applications (eg, sensors, fuel cells).

[0034] As used herein, "formation" is a process that includes the step of charging the battery for the first time. This charging can be done using a "formation current." An "unformed" structure has not yet undergone the first charge of the "formation" process.

[0035] One embodiment of the present invention provides a method for forming an electrochemical device. The method may include: (a) exposing anode material particles to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the anode material particles; (b) forming a slurry comprising coated anode material particles; (c) casting the slurry on a surface to form a layer; (d) calendering the layer to form an anode of the electrochemical device; (e) placing a separator between the anode and the cathode to form a unit cell structure; and (f) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the anode. An exemplary solvent that can form a solid electrolyte interface on the anode can be a carbonate, such as ethylene carbonate. Step (a) may further include: exposing the anode material particles to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the anode material particles. In the method, the coating may include Li3BO3-Li2CO3.

[0036] In this embodiment of the method, the lithium-containing precursor may include a lithium alkoxide. The boron-containing precursor may include a boroalkoxide. The oxygen-containing precursor may be selected from: ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof. The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor may be in a gaseous state.

[0037] In this embodiment of the method, the anode material particles may be graphite particles. The cathode may include cathode material particles selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, vanadium; and the liquid electrolyte may include a lithium compound in an organic solvent.

[0038] In this embodiment of the method, the method may further include: applying a formation current to the unit cell structure in a first cycle of the formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%. In one embodiment of the method, the method may further include: applying a formation current to the unit cell structure in additional cycles of the formation process, so that the total number of cycles of the first cycle and the additional cycle is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

[0039] In this embodiment of the method, the coating may be a film having a thickness of 0.1 to 50 nanometers.Step (a) may occur at a temperature between 50°C and 280°C.

[0040] In this embodiment of the method, the liquid electrolyte may include a lithium compound in an organic solvent. The lithium compound may be selected from LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2(LiTFSI), and LiCF3SO3(LiTf), and the organic solvent may be selected from carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof. The organic solvent may be selected from dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof. The liquid electrolyte may include LiPF6 and ethyl methyl carbonate.

[0041] Another embodiment of the present invention provides a method for forming an electrochemical device. The method may include: (a) forming a mixture containing particles of an anode material; (b) casting and / or calendering the mixture to form a porous structure; (c) exposing the porous structure to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the porous structure, thereby forming an anode; (d) placing a separator between the anode and the cathode to form a unit cell structure; and (e) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the anode. An exemplary solvent that can form a solid electrolyte interface on the anode can be a carbonate, such as ethylene carbonate. Step (c) may further include: exposing the porous structure to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the porous structure. In the method, the coating may include Li3BO3-Li2CO3.

[0042] In this embodiment of the method, the lithium-containing precursor may include a lithium alkoxide. The boron-containing precursor may include a boroalkoxide. The oxygen-containing precursor may be selected from ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof. The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor may be in a gaseous state.

[0043] In this embodiment of the method, the anode material particles may be graphite particles. The cathode may include cathode material particles selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium; and the liquid electrolyte may include a lithium compound in an organic solvent.

[0044] In this embodiment of the method, the method may further include: applying a formation current to the unit cell structure in a first cycle of the formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%. In one embodiment of the method, the method may further include: applying a formation current to the unit cell structure in additional cycles of the formation process, so that the total number of cycles of the first cycle and the additional cycle is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

[0045] In this embodiment of the method, the coating may be a film having a thickness of 0.1 to 50 nanometers.Step (a) may occur at a temperature between 50°C and 280°C.

[0046] In this embodiment of the method, the liquid electrolyte may include a lithium compound in an organic solvent. The lithium compound may be selected from LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2(LiTFSI), and LiCF3SO3(LiTf), and the organic solvent may be selected from carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof. The organic solvent may be selected from: dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof. The liquid electrolyte may include LiPF6 and ethyl methyl carbonate.

[0047] Another embodiment of the present invention provides a method for forming an electrochemical device. The method may include: (a) exposing cathode material particles to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the cathode material particles; (b) forming a slurry containing coated cathode material particles; (c) casting the slurry on a surface to form a layer; (d) calendering the layer to form a cathode of the electrochemical device; (e) placing a separator between the cathode and the anode to form a unit cell structure; and (f) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the cathode. An exemplary solvent that can form a solid electrolyte interface on the cathode can be a carbonate, such as ethylene carbonate. Step (a) may further include: exposing the cathode material particles to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the cathode material particles. In the method, the coating may include Li3BO3-Li2CO3.

[0048] In this embodiment of the method, the lithium-containing precursor may include a lithium alkoxide. The boron-containing precursor may include a boroalkoxide. The oxygen-containing precursor may be selected from ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof. The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor may be in a gaseous state.

[0049] In this embodiment of the method, the cathode material particles may be selected from lithium metal oxides and lithium-containing phosphates having the general formula LiMPO4, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium, wherein M is one or more of cobalt, iron, manganese, and nickel. In this embodiment of the method, the cathode material particles may be selected from lithium metal oxides and lithium-containing phosphates having the general formula LiMPO4, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium. a Mn b Co c Cathode material particles of O2, wherein a+b+c=1, and a:b:c=(NMC 111), a:b:c=4:3:3(NMC 433), a:b:c=5:2:2(NMC 522), a:b:c=5:3:2(NMC 532), a:b:c=6:2:2(NMC 622), or a:b:c=8:1:1(NMC 811).

[0050] In this embodiment of the method, the cathode material particles may be selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, vanadium; the anode may comprise graphite particles; and the liquid electrolyte may comprise a lithium compound in an organic solvent.

[0051] In this embodiment of the method, the method may further include: applying a formation current to the unit cell structure in a first cycle of the formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%. In one embodiment of the method, the method may further include: applying a formation current to the unit cell structure in additional cycles of the formation process, so that the total number of cycles of the first cycle and the additional cycle is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

[0052] In this embodiment of the method, the coating may be a film having a thickness of 0.1 to 50 nanometers.Step (a) may occur at a temperature between 50°C and 280°C.

[0053] In this embodiment of the method, the liquid electrolyte may include a lithium compound in an organic solvent. The lithium compound may be selected from LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2(LiTFSI), and LiCF3SO3(LiTf), and the organic solvent may be selected from carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof. The organic solvent may be selected from dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof. The liquid electrolyte may include LiPF6 and ethyl methyl carbonate.

[0054] Still another embodiment of the present invention provides a method for forming an electrochemical device. The method may include: (a) forming a mixture containing cathode material particles; (b) casting and / or calendering the mixture to form a porous structure; (c) exposing the porous structure to a lithium-containing precursor and then an oxygen-containing precursor to form a coating on the porous structure, thereby forming a cathode; (d) placing a separator between the cathode and the anode to form a unit cell structure; and (e) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of a solvent that forms a solid electrolyte interface on the cathode. An exemplary solvent that can form a solid electrolyte interface on the cathode can be a carbonate, such as ethylene carbonate. Step (c) may further include: exposing the porous structure to a boron-containing precursor and then the oxygen-containing precursor to form a coating on the porous structure. In the method, the coating may include Li3BO3-Li2CO3.

[0055] In this embodiment of the method, the lithium-containing precursor may include a lithium alkoxide. The boron-containing precursor may include a boroalkoxide. The oxygen-containing precursor may be selected from ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof. The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor may be in a gaseous state.

[0056] In this embodiment of the method, the cathode material particles may be selected from lithium metal oxides and lithium phosphates having the general formula LiMPO4, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium, wherein M is one or more of cobalt, iron, manganese, and nickel. In this embodiment of the method, the cathode material particles may be selected from lithium metal oxides and lithium phosphates having the general formula LiMPO4, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium. a Mn b Co cCathode material particles of O2, wherein a+b+c=1, and a:b:c=(NMC 111), a:b:c=4:3:3(NMC433), a:b:c=5:2:2(NMC522), a:b:c=5:3:2(NMC 532), a:b:c=6:2:2(NMC 622), or a:b:c=8:1:1(NMC811).

[0057] In this embodiment of the method, the cathode material particles may be selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, vanadium; the anode may comprise graphite particles; and the liquid electrolyte may comprise a lithium compound in an organic solvent.

[0058] In this embodiment of the method, the method may further include: applying a formation current to the unit cell structure in a first cycle of the formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%. In one embodiment of the method, the method may further include: applying a formation current to the unit cell structure in additional cycles of the formation process, so that the total number of cycles of the first cycle and the additional cycle is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

[0059] In this embodiment of the method, the coating may be a film having a thickness of 0.1 to 50 nanometers.Step (a) may occur at a temperature between 50°C and 280°C.

[0060] In this embodiment of the method, the liquid electrolyte may include a lithium compound in an organic solvent. The lithium compound may be selected from LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2(LiTFSI), and LiCF3SO3(LiTf), and the organic solvent may be selected from carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof. The organic solvent may be selected from dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof. The liquid electrolyte may include LiPF6 and ethyl methyl carbonate.

[0061] The present invention provides a method that eliminates the expensive natural SEI formation required during the formation process of a lithium ion battery having an anode comprising graphite and a liquid electrolyte comprising an ethylene carbonate solvent. In an embodiment of the method of the present invention, the electrolyte is substantially free of solvents that can form a solid electrolyte interface (SEI) on the anode and / or cathode. In another embodiment of the method of the present invention, the electrolyte is substantially free of solvents that can form a solid electrolyte interface on the anode and / or cathode, such as carbonates that can form a solid electrolyte interface on the anode and / or cathode. In another embodiment of the present invention, the electrolyte is substantially free of ethylene carbonate that can form a solid electrolyte interface on the anode and / or cathode. As used herein, "substantially free of solvents that form a solid electrolyte interface" means that no solvent that can form a solid electrolyte interface is added to the electrolyte, but the solvent that can form a solid electrolyte interface may be present in the electrolyte as an impurity or undesirable contaminant. For example, "substantially free of ethylene carbonate" means that ethylene carbonate is not added to the electrolyte, but ethylene carbonate may be present in the electrolyte as an impurity or undesirable contaminant.

[0062] One embodiment described herein relates to a method of producing a lithium-ion battery using atomic layer deposition (ALD). The lithium-ion battery may be a liquid electrolyte-based lithium-ion battery.

[0063] In one non-limiting example application, atomic layer deposition can be used to form Figure 1 The thin film lithium ion battery 110 shown in FIG. The thin film lithium ion battery 110 includes a current collector 112 (e.g., aluminum) in contact with a cathode 114. A separator 116 is disposed between the cathode 114 and an anode 118, and the anode 118 is in contact with a current collector 122 (e.g., aluminum). The current collectors 112 and 122 of the thin film lithium ion battery 110 may be electrically connected to an electrical component 124. The electrical component 124 may electrically connect the thin film lithium ion battery 110 to an electrical load that discharges the battery or a charger that charges the lithium ion battery.

[0064] The electrolyte of the battery 110 may be a liquid electrolyte. The liquid electrolyte of the electrochemical cell may include a lithium compound in an organic solvent. The lithium compound may be selected from LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2 (LiTFSI), and LiCF3SO3 (LiTf). The organic solvent may be selected from carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof. The carbonate-based solvent may be selected from dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, propylene carbonate, and butylene carbonate; while the ether-based solvent is selected from diethyl ether, dibutyl ether, monoglyme, diglyme, tetraglyme, 2-methyltetrahydrofuran, tetrahydrofuran, 1,3-dioxolane, 1,2-dimethoxyethane, and 1,4-dioxane. The liquid electrolyte is substantially free of solvents that can form a solid electrolyte interface (SEI) on the anode and / or cathode.

[0065] The first current collector 112 and the second current collector 122 may include a conductive metal or any suitable conductive material. In some embodiments, the first current collector 112 and the second current collector 122 include aluminum, nickel, copper, combinations thereof, and alloys. In other embodiments, the first current collector 112 and the second current collector 122 have a thickness of 0.1 micrometers or greater. It will be understood that Figure 1 The thickness depicted in is not drawn to scale, and the thickness of the first current collector 112 and the second current collector 122 may be different.

[0066] Suitable active materials for the cathode 114 of the thin film lithium ion battery 110 are lithium host materials capable of storing and subsequently releasing lithium ions. Exemplary cathode active materials are lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium. Non-limiting exemplary lithium metal oxides are: LiCoO2 (LCO), LiFeO2, LiMnO2 (LMO), LiMn2O4, LiNiO2 (LNO), LiNi x Co y O2、LiMn x Co y O2、LiMn x Ni y O2、LiMn x Ni y O4、LiNi x Co y Al z O2、LiNi 1 / 3 Mn 1 / 3 Co1 / 3 O2 and the like. Other examples of cathode active materials are lithium-containing phosphates having the general formula LiMPO4, wherein M is one or more of cobalt, iron, manganese, and nickel, such as lithium iron phosphate (LFP) and lithium iron fluorophosphate. Another example of a cathode active material is V2O5. Various different elements, such as Co, Mn, Ni, Cr, Al, or Li, may be added to the structure alternatively or additionally to affect the conductivity, layer order, stability during delithiation, and cycle performance of the cathode material. The cathode active material may be selected from a material having the formula LiNi a Mn b Co c Cathode material particles of O2, wherein a+b+c=1, and a:b:c=(NMC 111), a:b:c=4:3:3(NMC 433), a:b:c=5:2:2(NMC 522), a:b:c=5:3:2(NMC 532), a:b:c=6:2:2(NMC 622), or a:b:c=8:1:1(NMC 811). The cathode active material may be a mixture of any number of these cathode active materials. In other embodiments, suitable materials for the cathode 114 of the thin film lithium ion battery 110 are porous carbon (for lithium air batteries), or sulfur-containing materials (for lithium sulfur batteries).

[0067] In some embodiments, suitable active materials for anode 118 of thin film lithium ion battery 110 include materials selected from the group consisting of graphite, lithium titanate, hard carbon, tin / cobalt alloys, silicon, and silicon-carbon composites.

[0068] The thin film lithium ion battery 110 includes a separator 116 located between a cathode 114 and an anode 118. An exemplary separator 116 material for the thin film lithium ion battery 110 may be a permeable polymer, such as a polyolefin. Exemplary polyolefins include polyethylene, polypropylene, and combinations thereof. The thickness of the separator 116 may be in the range of 1 to 200 nanometers, or in the range of 40 to 1000 nanometers.

[0069] Figure 2A process flow chart 300 of a method for preparing an ion-conducting membrane using the atomic layer deposition process of the present invention is described. The method may include a first step in which a substrate is exposed to a lithium-containing precursor, which reacts with a surface and removes excess and product species from the surface. Subsequently, an oxygen-containing precursor is exposed to the surface and additional reactions occur. This represents a single "subcycle" that can be repeated x times, where x can be any integer from 1 to 10. Subsequently, the following subcycle can be repeated y times, in which a boron-containing precursor and then an oxygen-containing precursor are exposed to the substrate, where y can be any integer from 1 to 10. Subsequently, the entire "supercycle" z times can be repeated to deposit a layer of desired thickness. The value of z can be an integer between 1 and 5000, between 10 and 1000, or between 100 and 500. The process can result in the formation of a film comprising lithium, boron and oxygen (and in some cases carbon). The precursors can be in a gaseous state. The subcycles can occur in any order to initiate the supercycle. Continuous reactions can be separated in time or in space.

[0070] The lithium-containing precursor may be selected from lithium tert-butoxide (LiO t The precursor containing lithium may be selected from the group consisting of triisopropyl borate (TIB), boron tribromide (BBr3), boron trichloride (BCl3), triethyl boron (TEB), tri(ethyl-methylamino) borane, trichloroborazine (TCB), tri(dimethylamino) borane (TDMAB), trimethyl borate (TMB), and diboron tetrafluoride (B2F4). The precursor containing boron may be a borane oxide, such as triisopropyl borate. The precursor containing oxygen may be selected from the group consisting of ozone (O3), water (H2O), oxygen plasma (O2(p)), ammonium hydroxide (NH4OH), and oxygen (O2). The precursor containing oxygen may be ozone.

[0071] The film formed by method 300 is an artificial solid electrolyte interface (a-SEI). Studies have shown that the conformal ALD film eliminates the expensive natural SEI formation required during the formation process of a lithium-ion battery having an anode containing graphite and a liquid electrolyte containing an ethylene carbonate solvent. In addition, a unit cell having a graphite electrode coated with the film exhibits superior rate capability and stability during fast charging of a lithium-ion battery using an electrolyte without ethylene carbonate.

[0072] The thickness of the membrane formed by method 300 may be between 20 and 100 nm, between 0.1 and 1000 nm, between 1 and 100 nm, between 20 and 80 nm, between 0.1 and 50 nm, or between 0.1 and 35 nm. The area specific-resistance (ASR) of the ion-conducting membrane layer may be less than 450 ohm cm 2 , or less than 400ohm cm 2 , or less than 350ohm cm 2 , or less than 300ohm cm 2 , or less than 250ohmcm 2 , or less than 200 ohm cm 2 , or less than 150ohmcm 2 , or less than 100 ohm cm 2 , or less than 75ohm cm 2 , or less than 50ohm cm 2 , or less than 25ohm cm 2 , or less than 10 ohm cm 2 , or less than 5Ω-cm 2 .

[0073] The ionic conductivity of the membrane formed by the method 300 at standard temperature and pressure may be greater than 1.0 x 10 -7 S / cm, or greater than 1.0x 10 -6 S / cm, or greater than 1.5x 10 -6 S / cm, or greater than 2.0x 10 -6 S / cm, or greater than 2.2 x 10 -6 S / cm. The ion transfer number of the ion conductive layer can be greater than 0.9999 at 0-6 volts relative to lithium metal. The first step and the second step can be performed in any order and at a temperature between 50°C and 280°C, between 180°C and 280°C, or between 200°C and 220°C.

[0074] The substrate in method 300 may be an anode or a cathode. The substrate in method 300 may be planar, or may have a three-dimensional structure, such as a corrugated structure.

[0075] Forming electrodes for electrochemical devices

[0076] The present disclosure relates to forming electrodes used in electrochemical devices (e.g., lithium ion batteries). In one embodiment, a method of forming an electrode comprises depositing a film of the present disclosure on a powdered electrode material and forming a slurry comprising the coated electrode material. The slurry is then cast on a surface to form a layer, and the layer is dried and rolled to form the electrode. The electrode material may be any of the anode material or cathode material described above.

[0077] In another embodiment, the electrode can be produced by forming a slurry containing the electrode material, casting the slurry on a surface to form a layer, and drying and calendering the layer. Subsequently, the membrane of the present disclosure is deposited on the surface of the dried and calendered layer to form a thin film, thereby completing the electrode formation.

[0078] In another embodiment, the electrode can be produced by forming a slurry containing electrode materials, casting the slurry on a surface to form a layer, calendering the layer, and depositing the film of the present disclosure on the layer. Subsequently, the film-coated layer is dried and calendered to complete the electrode formation.

[0079] The slurry as described in any of the foregoing embodiments can be formed by mixing the electrode material or the coated electrode material with an aqueous or organic solvent. Suitable solvents may include N-methyl-2-pyrrolidone (NMP) or other suitable substitutes readily understood by those skilled in the art. A binder may also be added to the slurry, such as polyvinylidene fluoride (PVDF) or any suitable substitute readily understood by those skilled in the art. Conductive additives such as metal powders or carbon black may also be added to the slurry.

[0080] The layer of the electrode as described in any of the preceding embodiments can be dried and calendered to have a thickness ranging from 1 to 200 microns. In some embodiments, the thickness of the electrode is less than 175 microns, or less than 150 microns, or less than 125 microns, or less than 100 microns, or less than 75 microns, or less than 50 microns.

[0081] The thickness of the thin film coating on the surface of the electrode material as described in any of the preceding embodiments may range from 0.1 to 50 nanometers. An exemplary thin film coating comprises Li3BO3-Li2CO3.

[0082] Example

[0083] The following examples are provided to demonstrate and further illustrate certain embodiments and aspects of the present invention and should not be construed as limiting the scope of the present invention. The statements in the examples are provided without being bound by theory.

[0084] Example 1

[0085] A. Summary of Example 1

[0086] Achieving fast charging (≥4C) of lithium-ion batteries is an important challenge to accelerate the adoption of electric vehicles. (The C rate indicates how quickly a battery is charged or discharged. For example, at 1C, the battery is charged and discharged at a current equivalent to the battery's ampere-hour (Ah) rating. At 4C, the battery is charged and discharged at a current four times the 1C rate.) However, the desire to maximize energy density has driven the use of increasingly thicker electrodes, which has hindered power density. Here, a single ion-conducting solid electrolyte (Li3BO3-Li2CO3) film is coated onto a calendered graphite electrode using atomic layer deposition to form an artificial solid electrolyte interface (a-SEI). Compared to an uncoated control electrode, the solid electrolyte coating: (1) eliminates natural SEI formation during preconditioning from the expensive formation process; (2) increases the coulombic efficiency of the battery after the first cycle of the formation process; and (3) increases the average coulombic efficiency after the application of the formation current for multiple cycles of the formation process.

[0087] Lithium-ion batteries (LIBs) have become an essential part of society for storing and using electrical energy. Among numerous applications, electric vehicles (EVs) are rapidly becoming the main source of demand for rechargeable batteries. Despite significant progress in the past few years, further increasing the charging rate remains a major challenge. To date, most work on fast charging of graphite has been aimed at achieving uniform current distribution throughout the thickness of the electrode by improving mass transfer in the electrolyte.

[0088] While these works have shown great promise in achieving fast charging and demonstrated the importance of mass transfer, little attention has been paid to the role of the solid electrolyte interface (SEI) in determining fast charging performance. In state-of-the-art LIBs, a mosaic SEI composed of inorganic and organic species is naturally formed during initial charge due to electrolyte decomposition as the graphite electrode potential decreases to the equilibrium potential of lithium metal (-3.04 V relative to SHE) [References 1-3]. The primary means of engineering the SEI is through electrolyte modification, which has proven to be a key driver of the high coulombic efficiency and long cycle life achieved in today's LIBs [Reference 4]. When the electrochemical potential is held relative to Li / Li + >0 V, the properties of the native SEI are adequate at low current densities but cannot prevent Li plating during fast charging.

[0089] While artificial SEI (a-SEI) coatings have been investigated for improving interfacial stability, less attention has been paid to optimizing the a-SEI for fast charging. We have recently developed an atomic layer deposition (ALD) process for single ion conducting solid electrolytes that remain stable to Li [Refs 5-6]. In particular, ALD of glassy Li3BO3-Li2CO3 (LBCO) solid electrolytes has been shown to exhibit these properties. LBCO films have been shown to have the highest measured ionic conductivity of any ALD film reported to date (>2x10 at 30°C). -6 S / cm) and remain stable when cycled in contact with lithium metal [Ref. 7].

[0090] Due to the self-limiting nature of surface reactions, ALD provides unparalleled control over film thickness and conformality. ALD is a powerful means of interface modification of electrode materials in LIBs, but work to date has focused primarily on coating cathodes to improve interface stability.

[0091] Herein, we present the use of a single ion conducting solid electrolyte (LBCO) coating on graphite electrodes. The study shows that conformal ALD films can eliminate the expensive natural SEI formation required during the formation process of lithium-ion batteries (which have an anode comprising graphite and a liquid electrolyte comprising ethylene carbonate solvent). In addition, during fast charging of lithium-ion batteries using electrolytes without ethylene carbonate, unit cells with graphite electrodes coated with the film show superior rate performance and stability. This Example 1 points out the key role of SEI in limiting the fast charging capability of LIBs.

[0092] B. Experimental Methods

[0093] Electrode Fabrication: Graphite and NMC electrodes were fabricated using the pilot-scale roll-to-roll battery fabrication facility at the University of Michigan Battery Laboratory as described previously [Ref 8]. Graphite electrodes were fabricated with a total loading of 9.40 mg cm -2 , including 94% natural graphite (battery grade, SLC1506T, premium graphite), 1% C65 conductive additive, and 5% CMC / SBR binder), resulting in a theoretical capacity of 3.18 mAh-cm -2 The electrode was calendered to a porosity of ~32%. After coating, drying, calendering and punching, the entire electrode was moved to a Savannah S200 ALD reactor integrated into an argon glove box for coating.

[0094] Using LiNi 0.5 Mn 0.3 Co 0.2O2 (battery grade, NMC-532, Toda America) was used as the cathode material. The cathode formulation was 92 wt% NMC-532, 4 wt% C65 conductive additive, and 4 wt% PVDF binder. The cathode slurry was cast onto aluminum foil (15 μm thick) with a total areal mass loading of 16.58 mg-cm -2 , followed by calendering to 35% porosity. This gives an N:P ratio of 1.1-1.2.

[0095] Film Deposition and Characterization: LBCO ALD films were deposited onto graphite electrodes using a modified version of a previously reported ALD process [Ref 9]. The process used lithium tert-butoxide, triisopropyl borate, and ozone precursors. In this case, the lithium tert-butoxide pulse length was increased to 10 seconds with a 20 second exposure, and the triisopropyl borate pulse was increased to 0.25 seconds with a 20 second exposure. These modifications were made to enable complete coating of high surface area electrode substrates. Deposition was performed at a substrate temperature of 200°C. Film thickness was measured using spectroscopic ellipsometry on a silicon wafer placed near the graphite electrode. Data were collected using a Woollam M-2000 and then fitted by a Cauchy layer on top of the native oxide of Si. The LBCO ALD film thickness was approximately 20 nm.

[0096] Cell Assembly: 2032 coin cells were assembled by punching circular electrodes from larger pieces of ALD coated and control electrodes. These electrodes were placed into unit cells followed by Entek EPH separator, 75 μL electrolyte (1M LiPF6 in ethyl methyl carbonate), NMC electrodes, stainless steel spacers and Belleville washer. The unit cells were crimped at 1000 psi pressure.

[0097] Electrochemical characterization: Preconditioning and cycling were performed using a Landt 2001a battery test system.

[0098] C. Results and Discussion

[0099] We developed a coating process that deposits a protective LBCO coating on the electrode surface prior to unit cell assembly. The LBCO coating deposited by atomic layer deposition contains a lithium borate-lithium carbonate solid electrolyte.

[0100] Figure 3The following is depicted: SEI formation on graphite is eliminated by LBCO coating in an electrolyte without ethylene carbonate (EC) (in panels a and b), and the initial pre-conditioning cycle Coulombic efficiency (in panel c). The coating passivates the electrode surface, preventing side reactions during charging and improving the first cycle efficiency (see Figure 3 , small pictures ac).

[0101] Lithium-ion batteries containing graphite-based materials as negative electrodes are generally designed so that the reversible capacity (N) of the negative electrode is greater than the reversible capacity (P) of the positive electrode. The N:P ratio is then defined. Typically, this type of battery is designed with an N:P ratio > 1 (e.g. 1.05-1.3). Therefore, excess graphite is placed in the unit cell to prevent lithium plating at the negative electrode during the charge and discharge cycles, which leads to battery degradation. However, this excess graphite leads to a decrease in the specific energy density of the unit cell. The LBCO artificial SEI reduces the impedance of the electrode compared to the natural SEI. Therefore, the LBCO coating enables the use of lower N:P ratios without the presence of lithium plating. This involves Figure 3 . Charging at 4.3V and 4.5V increases the accessed capacity of the positive electrode while leaving the capacity of the negative electrode unchanged. This therefore reduces the N:P ratio and increases the energy density. The results suggest that the LBCO coating enables improved capacity retention under these conditions by preventing lithium plating.

[0102] Figure 4 Depicted below are the capillary rise of a carbonate-based electrolyte through a rolled electrode, measured by optical image analysis (panel a), and images of the electrode immersed in the electrolyte, initially and after 200 seconds (panels b and c). Eliminating SEI formation also reduces the need for slow, expensive preconditioning after cell assembly. The LBCO coating also improves the wettability of the electrode by the electrolyte (see Figure 4 ), reducing the time required before preconditioning can begin.

[0103] Figure 5 The following are plotted: discharge capacity at upper cutoff voltages of 4.3 V and 4.5 V, and average coulombic efficiency for the first 50 cycles at 1C / 1C charge / discharge rate at upper voltage cutoffs of 4.3 V and 4.5 V (inset c) with and without LBCO coating. The LBCO coating allows the use of EC-free electrolytes without additives, thus improving the high cutoff voltage (4.3-4.5 V, see Figure 5 , Figure ac) shows the cyclic stability under the conditions.

[0104] Example 2

[0105] A. Overview of Example 2

[0106] Another potential benefit of an artificial SEI like LBCO is related to the preconditioning process. The present invention reduces the need for preconditioning. However, in some cases, the preconditioning process also affects the interface formation on the positive electrode. Therefore, the relaxation of the preconditioning requirements associated with graphite negative electrodes can open up new possibilities for improving the performance / properties of the cathode electrolyte interface (sometimes referred to as CEI) formed on the positive electrode. For example, the optimal conditions for preconditioning a graphite-based anode may be different from the optimal conditions for the positive electrode (for example, the positive electrode may include LiNi a Mn b Co c O2, where a+b+c=1 and a:b:c=5:3:2 (NMC 532)). In this case, we can improve the performance by optimizing the positive electrode without sacrificing the SEI formation process on graphite-based anodes, because we have put an artificial SEI in place on the anode.

[0107] B. Experimental Methods, Results and Discussion

[0108] We collected X-ray photoelectron spectroscopy data that showed one benefit of implementing an ethylene carbonate-free electrolyte, which is related to transition metal dissolution from the NMC positive electrode. The positive electrode was prepared as in Example 1. Figure 6 As shown in , the electrode has significantly weakened signals for Ni 2p, Co 2p, and Mn 2p peaks when only ethyl methyl carbonate (EMC) electrolyte is used (without EC). This is attributed to the elimination of the reaction mechanism involving the dehydrogenation of ethylene carbonate (EC) at the surface of the NMC positive electrode. This allows for an EC-free electrolyte as it can suppress the disadvantages associated with EC reactivity.

[0109] Example 3

[0110] We explored another approach to achieve EC-free electrolytes. Figure 7 High voltage cycling data for LBCO coated graphite in an ethylene carbonate free electrolyte prepared as in Example 1 is shown, as well as uncoated electrodes in an ethylene carbonate free electrolyte with and without 2% vinyl carbonate (VC) additive, and a conventional (ethylene carbonate containing) electrolyte with VC additive. It has been shown that the VC additive has helped to form a stable SEI in the absence of ethylene carbonate, thus enabling more stable cycling in the ethylene carbonate free electrolyte. Figure 7In the curves of , we show that the performance of LBCO coating is better than all other cases, including VC additive. Therefore, in addition to other benefits of the coating method compared to electrolyte modification (e.g., elimination of pre-conditioning process), LBCO coating provides greater stability improvement compared to what is probably the most commonly explored / reported method (i.e., using VC additive).

[0111] Example 4

[0112] In the present disclosure, we note that electrolytes without ethylene carbonate can have higher ionic conductivity. Another important related aspect of the present disclosure is the operating temperature range of lithium ion batteries. The freezing point of ethylene carbonate is much higher than other carbonates, which means that when ethylene carbonate is a component in the electrolyte, low temperature operation is limited. The freezing points are shown in Table 1 below for reference.

[0113] Table 1

[0114] Freezing point Ethylene carbonate (EC) 36.4℃ Ethyl Methyl Carbonate(EMC) -14℃ Propylene carbonate (PC) -48.8℃ Dimethyl carbonate (DMC) 2-4℃ Diethyl carbonate (DEC) -43℃ Vinylene carbonate (VC) 22℃ Fluoroethylene carbonate (FEC) 18-23℃

[0115] Therefore, the LBCO artificial SEI shown in these examples also improves the high temperature operation of lithium-ion batteries. At elevated temperatures (e.g., 50°C), successive side reactions (associated with SEI and CEI growth) are accelerated. LBCO passivates the electrode and inhibits these side reactions, thereby improving capacity retention.

[0116] References

[0117] 1.Peled, et al., "Advanced Model for Solid Electrolyte Interphase Electrodes in Liquid and Polymer Electrolytes", J. Electrochem. Soc. 144, L208–L210 (1997).

[0118] 2.Peled, "The Electrochemical Behavior of Alkali and Alkaline EarthMetals in Nonaqueous Battery Systems—The Solid Electrolyte Interphase Model", J. Electrochem. Soc. 126, 2047–2051 (1979).

[0119] 3.Aurbach et al.,"On the correlation between surface chemistryandperformance of graphite negative electrodes for Liion batteries",Electrochim.Acta45,67–86(1999).

[0120] 4.Xu,"Electrolytes and interphases in Li-ion batteries and beyond",Chem.Rev.114,11503–11618(2014).

[0121] 5.Kazyak et al.,"Atomic layer deposition and first principlesmodeling ofglassy Li3BO3–Li2CO3 electrolytes for solid-state Li metalbatteries",J.Mater.Chem.A 6,19425–19437(2018).

[0122] 6.Kazyak et al.,"Atomic Layer Deposition of the Solid ElectrolyteGarnetLi7La3Zr2O 12 ",Chem.Mater.29,3785–3792(2017).

[0123] 7.Kazyak et al.,"Atomic layer deposition and first principlesmodeling ofglassy Li3BO3-Li2CO3 electrolytes for solid-state Li metalbatteries",J.Mater.Chem.A 6,19425–19437(2018).

[0124] 8. Chen et al., "Efficient fast-charging of lithium-ion batteries enabled by laser-patterned three-dimensional graphite anode architectures", J. Power Sources471, 228475 (2020).

[0125] 9.Kazyak et al., "Atomic layer deposition and first principles modeling of glassy Li3BO3-Li2CO3 electrolytes for solid-state Li metalbatteries", J.Mater.Chem.A 6, 19425–19437(2018).

[0126] The citation of any document shall not be construed as an admission that it is prior art to the present invention.

[0127] Thus, the present invention provides a coating process that deposits a protective coating on the surface of a lithium-ion battery electrode prior to cell assembly. The coating passivates the electrode surface, preventing side reactions during charging and improving first cycle efficiency. Eliminating SEI formation also reduces the need for slow, expensive preconditioning after lithium-ion battery cell assembly. The LBCO coating also improves electrolyte wetting into the electrode, reducing the time required before preconditioning can begin. The LBCO coating enables the use of EC-free electrolytes without additives, thereby improving the cycling stability of lithium-ion batteries at high voltages.

[0128] Based on the principles and exemplary embodiments described and illustrated herein, it will be appreciated that the exemplary embodiments may be modified in settings and details without departing from these principles. In addition, the above discussion focuses on specific embodiments, but other configurations are also considered. In particular, although expressions such as "in one embodiment", "in another embodiment", etc. are used herein, these expressions are intended to generally refer to the possibility of embodiments and are not intended to limit the present invention to specific embodiment configurations. As used herein, these terms may represent the same or different embodiments that can be combined into other embodiments. As a rule, any embodiment cited herein can be freely combined with any one or more other embodiments cited herein, and any number of features of different embodiments can be combined with each other, unless otherwise stated.

[0129] Although the present invention has been described in considerable detail with reference to certain embodiments, those skilled in the art will appreciate that the present invention may be practiced in embodiments other than those described, which are presented for illustrative purposes rather than for limiting purposes. Therefore, the scope of the appended claims should not be limited to the description of the embodiments contained herein. Various features and advantages of the present invention are set forth in the following claims.

Claims

1. A method of forming an electrochemical device, the method comprising: (a) exposing particles of anode material to a lithium-containing precursor followed by an oxygen-containing precursor to form a coating on the particles of anode material; (b) forming a slurry comprising coated anode material particles; (c) casting the slurry on a surface to form a layer; (d) calendaring the layer to form an anode of the electrochemical device; (e) placing a separator between the anode and the cathode to form a unit cell structure; as well as (f) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of solvent that forms a solid electrolyte interface on the anode.

2. The method of claim 1, wherein step (a) further comprises: exposing the anode material particles to a boron-containing precursor followed by the oxygen-containing precursor to form a coating on the anode material particles.

3. The method of claim 1, wherein: The lithium-containing precursor includes a lithium alkoxide.

4. The method of claim 2, wherein: The boron-containing precursor comprises a borane oxide.

5. The method of claim 1, wherein: The oxygen-containing precursor is selected from the group consisting of ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof.

6. The method of claim 2, wherein: The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor are in a gaseous state.

7. The method of claim 1, wherein: The anode material particles are graphite particles.

8. The method of claim 7, wherein: The cathode comprises cathode material particles selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium, and The liquid electrolyte comprises a lithium compound in an organic solvent.

9. The method of claim 8, further comprising: (g) applying a formation current to the unit cell structure in a first cycle of a formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%.

10. The method of claim 9, further comprising: (h) applying the formation current to the unit cell structure in additional cycles of the formation process such that the total number of cycles of the first cycle and the additional cycles is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

11. The method of claim 1, wherein: The solvent forming the solid electrolyte interface on the anode is ethylene carbonate.

12. The method of claim 1, wherein: The coating is a film having a thickness of 0.1 to 50 nanometers.

13. The method of claim 1, wherein: Step (a) occurs at a temperature between 50°C and 280°C.

14. The method of claim 1, wherein: The liquid electrolyte comprises a lithium compound in an organic solvent.

15. The method of claim 14, wherein: The lithium compound is selected from the group consisting of LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2 (LiTFSI), and LiCF3SO3 (LiTf), and The organic solvent is selected from the group consisting of carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof.

16. The method of claim 15, wherein: The organic solvent is selected from the group consisting of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl methyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof.

17. The method of claim 1, wherein: The liquid electrolyte includes LiPF6 and ethyl methyl carbonate.

18. The method of claim 1, wherein: The coating layer contains Li3BO3-Li2CO3.

19. A method of forming an electrochemical device, the method comprising: (a) forming a mixture comprising particles of an anode material; (b) casting and / or calendering the mixture so as to form a porous structure; (c) exposing the porous structure to a lithium-containing precursor and subsequently an oxygen-containing precursor to form a coating on the porous structure, thereby forming an anode; (d) placing a separator between the anode and the cathode to form a unit cell structure; as well as (e) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of solvent that forms a solid electrolyte interface on the anode.

20. The method of claim 19, wherein step (c) further comprises exposing the porous structure to a boron-containing precursor followed by the oxygen-containing precursor to form a coating on the porous structure.

21. The method of claim 19, wherein: The lithium-containing precursor includes a lithium alkoxide.

22. The method of claim 20, wherein: The boron-containing precursor comprises a borane oxide.

23. The method of claim 19, wherein: The oxygen-containing precursor is selected from the group consisting of ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof.

24. The method of claim 20, wherein: The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor are in a gaseous state.

25. The method of claim 19, wherein: The anode material particles are graphite particles.

26. The method of claim 25, wherein: The cathode comprises cathode material particles selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium, and The liquid electrolyte comprises a lithium compound in an organic solvent.

27. The method of claim 26, further comprising: (f) applying a formation current to the unit cell structure in a first cycle of a formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%.

28. The method of claim 27, further comprising: (g) applying a formation current to the unit cell structure in additional cycles of the formation process such that the total number of cycles of the first cycle and the additional cycles is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

29. The method of claim 19, wherein: The solvent forming the solid electrolyte interface on the anode is ethylene carbonate.

30. The method of claim 19, wherein: The coating is a film having a thickness of 0.1 to 50 nanometers.

31. The method of claim 19, wherein: Step (a) occurs at a temperature between 50°C and 280°C.

32. The method of claim 19, wherein: The liquid electrolyte comprises a lithium compound in an organic solvent.

33. The method of claim 32, wherein: The lithium compound is selected from the group consisting of LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2 (LiTFSI), and LiCF3SO3 (LiTf), and The organic solvent is selected from the group consisting of carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof.

34. The method of claim 33, wherein: The organic solvent is selected from the group consisting of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl methyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof.

35. The method of claim 19, wherein: The liquid electrolyte includes LiPF6 and ethyl methyl carbonate.

36. The method of claim 19, wherein: The coating layer contains Li3BO3-Li2CO3.

37. A method of forming an electrochemical device, the method comprising: (a) exposing cathode material particles to a lithium-containing precursor and subsequently an oxygen-containing precursor to form a coating on the cathode material particles; (b) forming a slurry comprising coated cathode material particles; (c) casting the slurry onto a surface to form a layer; (d) calendaring the layer to form a cathode of the electrochemical device; (e) placing a separator between the cathode and the anode to form a unit cell structure; as well as (f) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of solvent that forms a solid electrolyte interface at the cathode.

38. The method of claim 37, wherein step (a) further comprises: exposing the cathode material particles to a boron-containing precursor followed by the oxygen-containing precursor to form a coating on the cathode material particles.

39. The method of claim 37, wherein: The lithium-containing precursor includes a lithium alkoxide.

40. The method of claim 38, wherein: The boron-containing precursor comprises a borane oxide.

41. The method of claim 37, wherein: The oxygen-containing precursor is selected from the group consisting of ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof.

42. The method of claim 38, wherein: The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor are in a gaseous state.

43. A method as claimed in claim 37, wherein the cathode material particles are selected from lithium metal oxides and lithium phosphates having the general formula LiMPO4, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium, wherein M is one or more of cobalt, iron, manganese, and nickel.

44. The method of claim 37, wherein the cathode material particles are selected from particles having the formula LiNi a Mn b Co c Cathode material particles of O2, wherein a+b+c=1, and a:b:c=(NMC 111), a:b:c=4:3:3(NMC 433), a:b:c=5:2:2(NMC 522), a:b:c=5:3:2(NMC 532), a:b:c=6:2:2(NMC 622), or a:b:c=8:1:1(NMC811).

45. The method of claim 37, wherein: The cathode material particles are selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium. The anode comprises graphite particles, and The liquid electrolyte comprises a lithium compound in an organic solvent.

46. ​​The method of claim 45, further comprising: (g) applying a formation current to the unit cell structure in a first cycle of a formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%.

47. The method of claim 46, further comprising: (h) applying a formation current to the unit cell structure in additional cycles of the formation process such that the total number of cycles of the first cycle and the additional cycles is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

48. The method of claim 37, wherein the coating is a film having a thickness of 0.1 to 50 nanometers.

49. The method of claim 37, wherein: Step (a) occurs at a temperature between 50°C and 280°C.

50. The method of claim 37, wherein: The solvent forming the solid electrolyte interface on the cathode is ethylene carbonate.

51. The method of claim 37, wherein: The liquid electrolyte comprises a lithium compound in an organic solvent.

52. The method of claim 51, wherein: The lithium compound is selected from the group consisting of LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2 (LiTFSI), and LiCF3SO3 (LiTf), and The organic solvent is selected from the group consisting of carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof.

53. The method of claim 52, wherein: The organic solvent is selected from the group consisting of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl methyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof.

54. The method of claim 37, wherein: The organic solvent is selected from carbonate-based solvents, and mixtures thereof.

55. The method of claim 37, wherein: The liquid electrolyte includes LiPF6 and ethyl methyl carbonate.

56. The method of claim 37, wherein: The coating layer contains Li3BO3-Li2CO3.

57. A method of forming an electrochemical device, the method comprising: (a) forming a mixture comprising particles of a cathode material; (b) casting and / or calendering the mixture so as to form a porous structure; (c) exposing the porous structure to a lithium-containing precursor and subsequently an oxygen-containing precursor to form a coating on the porous structure, thereby forming a cathode; (d) placing a separator between the cathode and the anode to form a unit cell structure; as well as (e) placing the unit cell structure in a liquid electrolyte, wherein the electrolyte is substantially free of solvent that forms a solid electrolyte interface at the cathode.

58. The method of claim 57, wherein step (c) further comprises: exposing the porous structure to a boron-containing precursor followed by the oxygen-containing precursor to form a coating on the porous structure.

59. The method of claim 57, wherein: The lithium-containing precursor includes a lithium alkoxide.

60. The method of claim 58, wherein: The boron-containing precursor comprises a borane oxide.

61. The method of claim 57, wherein: The oxygen-containing precursor is selected from the group consisting of ozone, water, oxygen plasma, ammonium hydroxide, oxygen, and mixtures thereof.

62. The method of claim 58, wherein: The lithium-containing precursor, the boron-containing precursor, and the oxygen-containing precursor are in a gaseous state.

63. A method as claimed in claim 57, wherein the cathode material particles are selected from lithium metal oxides and lithium phosphates having the general formula LiMPO4, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium, wherein M is one or more of cobalt, iron, manganese, and nickel.

64. The method of claim 57, wherein the cathode material particles are selected from particles having the formula LiNi a Mn b Co c Cathode material particles of O2, wherein a+b+c=1, and a:b:c=(NMC 111), a:b:c=4:3:3(NMC 433), a:b:c=5:2:2(NMC 522), a:b:c=5:3:2(NMC 532), a:b:c=6:2:2(NMC 622), or a:b:c=8:1:1(NMC811).

65. The method of claim 57, wherein: The cathode material particles are selected from lithium metal oxides, wherein the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium. The anode comprises graphite particles, and The liquid electrolyte comprises a lithium compound in an organic solvent.

66. The method of claim 65, further comprising: (f) applying a formation current to the unit cell structure in a first cycle of a formation process, wherein after the first cycle, the coulombic efficiency of the unit cell structure is greater than 80%.

67. The method of claim 66, further comprising: (g) applying a formation current to the unit cell structure in additional cycles of the formation process such that the total number of cycles of the first cycle and the additional cycles is at least 50 cycles, wherein for the total number of cycles, the average coulombic efficiency after applying the formation current is greater than 99.5%.

68. The method of claim 57, wherein the coating is a film having a thickness of 0.1 to 50 nanometers.

69. The method of claim 57, wherein: Step (a) occurs at a temperature between 50°C and 280°C.

70. The method of claim 57, wherein: The solvent forming the solid electrolyte interface on the cathode is ethylene carbonate.

71. The method of claim 57, wherein: The liquid electrolyte comprises a lithium compound in an organic solvent.

72. The method of claim 71, wherein: The lithium compound is selected from: LiPF6, LiBF4, LiClO4, lithium bis(fluorosulfonyl)imide (LiFSI), LiN(CF3SO2)2 (LiTFSI), LiCF3SO3 (LiTf), and The organic solvent is selected from the group consisting of carbonate-based solvents, ether-based solvents, ionic liquids, and mixtures thereof.

73. The method of claim 72, wherein: The organic solvent is selected from the group consisting of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl methyl carbonate, propylene carbonate, butylene carbonate, and mixtures thereof.

74. The method of claim 57, wherein: The liquid electrolyte includes LiPF6 and ethyl methyl carbonate.

75. The method of claim 57, wherein: The coating layer contains Li3BO3-Li2CO3.